Identification of Human Papillomavirus Infection in Cancer Tissue by Targeted Next-generation Sequencing. Issue 7 (August 2016) - Montgomery, Nathan D.; Parker, Joel S.; Eberhard, David A.; Patel, Nirali M.; Weck, Karen E.; Sharpless, Norman E.; Hu, Zhiyuan; Hayes, David Neil; Gulley, Margaret L.
Abstract : Human papillomaviruses (HPV) are oncogenic DNA viruses implicated in squamous cell carcinomas of several anatomic sites, as well as endocervical adenocarcinomas. Identification of HPV is an actionable finding in some carcinomas, potentially influencing tumor classification, prognosis, and management. We incorporated capture probes for oncogenic HPV strains 16 and 18 into a broader next-generation sequencing (NGS) panel designed to identify actionable mutations in solid malignancies. A total of 21 head and neck, genitourinary, and gynecologic squamous cell carcinomas and endocervical adenocarcinomas were sequenced as part of the UNCSeq project. Using p16 immunohistochemical results as the gold standard, we set a cutoff for proportion of aligned HPV reads that maximized performance of our NGS assay (92% sensitive, 100% specific for HPV). These results suggest that sequencing of oncogenic pathogens can be incorporated into targeted NGS panels, extending the clinical utility of genomic assays.